Development of Finite Element Code for Non-Linear Analysis of Interlocking Mortarless Masonry System - Ahmed Al- Wathaf, Ahmed Hasan (2006)
Presently, interlocking mortarless masonry system has been developed as an alternative to the conventional mortared masonry system for wall construction. The structural behaviour of the interlocking mortarless masonry system is not well explored and there is no standard and/or design specification for safe design of the interlocking mortarless block masonry system. The existing finite element analyses are simplified due to the absence of the significant and essential structural characteristics of the interlocking mortarless masonry system. Hence these models show inaccurate prediction for the structural response of the masonry system compared to actual behaviour of the system found experimentally. This study aims at investigating numerically the structural response of interlocking masonry system using finite element method. The developed algorithm used in the FE analysis includes appropriate mathematical models to simulate the main features of mortarless masonry system. These models are derived experimentally using small scale specimens. The main features simulated are the structural characteristics of the interlocking dry joints under combined Normal-Shear force actions, the failure mechanism of the joints, nonlinear contact behaviour of the joint considering the geometric imperfection of the block beds, the nonlinear stress-strain behaviour of the masonry materials and the failure of the masonry materials as well as the geometric nonlinearity. Proper test setups have been proposed to measure accurately the joint response under elastic, inelastic and failure stages of load. The actual behaviour of the interlocking system obtained experimentally is mathematically modelled and implemented in the finite element algorithm developed for the analysis of the interlocking masonry system. An incremental-iterative 2-D nonlinear finite element code is developed to implement the proposed algorithm and analyze the masonry system till failure. The developed experimental setups used in this study successfully revealed the important features of the interlocking mortarless joint. The results indicate that the developed constitutive model and finite element code can successfully trace the structural behaviour (capacity, deformation and mode of failure) of the interlocking mortarless masonry system from the initial stage of loading till the failure. A general equation is proposed to estimate the capacity of interlocking mortarless masonry walls under eccentric and concentric vertical loads.